Purification and characterization of DNA ligase I from the trypanosomatid Crithidia fasciculata. - Brown, G W (1992)
A DNA ligase has been purified approximately 5000-fold, to near homogeneity, from the trypanosomatid Crithidia fasciculata. The purified enzyme contains polypeptides with molecular masses of 84 and 80 kDa as estimated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Both polypeptides formed enzyme-adenylate complexes in the absence of DNA, contained an epitope that is highly conserved between human and bovine DNA ligase I and yeast and vaccinia virus DNA ligases, and were identified in fresh lysates of C. fasciculata by antibodies raised against the purified protein. Hydrodynamic measurements indicate that the enzyme is an asymmetric protein of approximately 80 kDa. The purified DNA ligase can join oligo(dT) annealed to poly(dA), but not oligo(dT) annealed to poly(rA), and can ligate blunt-ended DNA fragments. The enzyme has a low Km for ATP of 0.3 microM. The DNA ligase absolutely requires ATP and Mg2+, and is inhibited by N-ethylmaleimide and by KCI. Substrate specificity, Km for ATP, and the conserved epitope all suggest that the purified enzyme is the trypanosome homologue of DNA ligase I.